A Review on Various Sniffing Attacks and its Mitigation Techniques - B. Prabadevi; N. Jeyanthi (Institute of Advanced Engineering and Science, 2018)
Security in the era of digital computing plays a vital role. Of various attacks in the field of computing, Distributed Denial of service (DDoS) attacks, Man-in-the-Middle Attack (MITM) and data theft have their major impact on the emerging applications. The sniffing attacks, one of the most prominent reasons for DDoS attacks, are the major security threats in the client-server computing. The content or packet sniffer snorts the most sensitive information from the network and alters or disturbs the legitimate functionality of the victim system. Therefore it is extremely important to have a greater knowledge on these vulnerabilities, their issues, and various mitigation techniques. This study analyses the existing sniffing attacks, variations of sniffing attacks and prevention or detection mechanisms. The reasons for most vital Ransomware are also discussed.